Continuidad académica universitaria en el AMBA, en contexto de emergencia económica y sanitaria: Estudio de caso, DHUCS, UNLAM - Laura Gomez Rusca; Marcelo Grifo; María Victoria; Marisol Villa (Atlantic Review of Economics (ARoEc), 2022)
– This research analyzes the academic continuity applied from the Department of Humanities and Social Sciences (DHuCS) of the National University of La Matanza, due to the implementation of mandatory isolation in the context of the COVID - 19 pandemic. The virtualization of the subject History of Argentine Education was taken as a specific case study. The course was held virtually through the use of platforms and the adaptatio n of materials, classes, as well as teacher - student communication. In this work, we affirm that the strategies applied in a context of public emergency, generated deep transformations in the way of providing and accessing education, allowing to guarantee t he academic - pedagogical continuity of a large part of the student body. In addition, this experience enriched the work of the University, which knew how to adapt positively to the vicissitudes of the context in which it was immersed.
Keywords: D; D7; D74; D78; I; I2; I23; 330